A QUALITATIVE DESCRIPTIVE ANALYSIS OF THE IMPLEMENTATION OF ANTI-VIOLENCE PROGRAMS IN ELEMENTARY SCHOOLS FOR BULLYING PREVENTION - Tiara Panduwinata; Dika Wulandari (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
Violence and bullying in school remain a critical issue within Indonesia’s educational system, despite the implementation of various anti-violence programs. This study aims to explore the dynamics of bullying practices and evaluate the effectiveness of anti-violence education from the perspectives of survivors, parents, and teachers. This study employs a qualitative descriptive approach supported by simple descriptive quantitative data. The qualitative data were obtained through in-depth interviews and documentation, while the quantitative data were drawn from a short descriptive questionnaire used to complement and strengthen the narrative findings. This design allows the researcher to describe participants’ experiences holistically while validating emerging patterns through basic numerical trends. The findings reveal that the most prevalent form of bullying is verbal abuse (40%), followed by social exclusion (30%), threats or intimidation (20%), and cyberbullying (10%). Thematic analysis indicates that victims often experience bullying because they are perceived as “different”—academically superior, introverted, or socially isolated—and that a permissive school culture and lack of empathy education contribute to the persistence of bullying. Approximately 80% of survivors reported intensified bullying after their parents lodged complaints, demonstrating the weakness of institutional empathy and protection mechanisms. These findings support the power imbalance theory (Olweus, 1993) and symbolic violence framework (Bourdieu, 1991), positioning bullying as a manifestation of social hierarchy and structural inequality within schools. The study underscores the need for empathic and restorative education that cultivates moral awareness rather than relying solely on administrative sanctions. Policy recommendations include the formation of school anti-violence task forces, integration of emotional literacy into the curriculum, and teacher training based on a humanistic pedagogical approach. Theoretically, this study contributes to the discourse on empathy-based anti-violence education, while practically it offers a conceptual model for developing a safe, inclusive, and humanizing educational ecosystem.